RESPONS DAN TINDAKAN KOMUNIKASI STRATEGIS STARTUP UNTUK MENGELOLA KOMENTAR NEGATIF - Titis Gandariani TGA (Jurnal Komunikasi & Media Digital, 2024)
Travelio is one of the start-up companies that frequently receives various negative comments on booking applications after providing services to consumers. This research attempts to identify the actions and communication responses of Travelio in managing negative comments. Using a case study method, this research collects data through observation, interviews, and literature review. The findings show that in managing negative comments, Travelio applies the concept of communication management, done through various phases. The communication actions and responses done are relevant to encountered conditions, namely using a proactive strategy and a reactive strategy approach. A specific approach is done towards interpersonal communication, advertising, and promotional media. Proactive strategy (organizational performance, audience participation, special events, alliances, and coalitions). Reactive strategy (defensive response strategies: (justification), vocal commiseration response strategies: apology, rectifying behavior response strategies: corrective action, diversionary response strategies: providing compensation after going through various steps (a) concession, (b) ingratiation, (c) disassociation.